Unusual one-step formation of Fe2O3/MnO2 core-shell hollow nanorods as a high performance anode material for lithium ion batteries - Hao, Shiji (2017)
In the present paper, we propose a facile method toward tuning the interior structure of Fe2O3/MnO2 core-shell nanorods. Through thermal annealing, Fe2O3/MnO2 hollow and Fe2O3/(Fe0.42Mn0.58)2O3/MnO2 solid core-shell nanorods are obtained under the condition of 500 and 600 °C, respectively. We demonstrate that the unusual internal structure transform corresponds to the inward movement of Mn element from the nanorods surface. Owing to the unique core-shell hollow nanostructure, Fe2O3/MnO2 nanorods show excellent electrochemical performances as anodes for lithium ion batteries, whose reversible capacity maintains more than 700 mAhg-1 after 2000 cycles.